Review of the Effects of Freezing/Thawing Cycles on the Engineering Properties of Soilcrete - Chao Liu; Claude Berard; Lijun Deng (Geotechnics, 2022)
Soil mixing, which blends the natural soils with cementitious materials (or binders), has been used to enhance the soft ground and improve problematic soils for several decades. With developments in technique and machinery, the embedded depth of soil mixing has increased from the shallow ground to as deep as tens of meters, especially when deep soil mixing and grouting emerged in the 1970s. Extensive studies have been undertaken on the physical and mechanical properties of the mixing products (soilcrete) with regard to water content, soil type, binder type, binder content, curing age, and curing condition. However, most studies initially focused on soil mixing in temperate weather. In recent decades, soil mixing in cold regions has become common. Thus, plenty of research has been conducted on the engineering properties of soilcrete exposed to weathering conditions in cold regions, namely freezing/thawing (F/T) cycles. However, while summaries of studies on soilcrete used in temperate conditions have been undertaken by researchers, reviews of studies on soil mixing in cold regions are still rare. In order to link potential research on soil mixing with previous studies and point out the possible research directions, a review of works on soilcrete subjected to F/T cycles was composed. The present paper summarizes the testing methods adopted by various studies and the change in engineering properties of soilcrete caused by F/T cycles.